Cinema and the republic: filming on the margins in contemporary France (French and francophone studies). - Ervine, Jonathan (French and francophone studies, 2013)
This book analyses contemporary French films by focussing closely on cinematic representations of immigrants and residents of suburban housing estates known as banlieues. It begins by examining how these groups are conceived of within France's Republican political model before analysing films that focus on four key issues. Firstly, it will assess representations of undocumented migrants known as sans-papiers before then analysing depictions of deportations made possible by the controversial double peine law. Next, it will examine films about relations between young people and the police in suburban France before exploring films that challenge cliches about these areas. The conclusion assesses what these films show about contemporary French political cinema.